Konsentrasi Hara, Serapan Hara dan Pertumbuhan pada Beberapa Varietas Kedelai dengan Aplikasi Paket Pemupukan Pupuk Hayati Mikoriza, Bahan Organik dan Anorganik di Lahan Kering - Wahyu Astiko; M Isnaini; MT Fauzi; I Muthahanas (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2021)
Astiko W, Isnaini M, Fauzi MT, Muthahanas I. 2021. Concentration, nutrient uptake and growth in several soybean varieties with application of mycorrhizal, organic and inorganic fertilizer package in dryland. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-9 Tahun 2021, Palembang 20 Oktober 2021. pp. 279-288. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).The application of inorganic fertilizers with high doses which are usually applied intensively by farmers can inhibit the development of mycorrhizae in the soil. Therefore, in its application it is necessary to set the appropriate dose for the development of mycorrhizae. Likewise, the addition of organic matter can stimulate the development of mycorrhizae in the soil. This study aims to determine the nutrient concentration, nutrient uptake, and growth of several soybean varieties with the application of inorganic fertilizer packages and organic matter and mycorrhizal biological fertilizers in dry land. This experiment used a Randomized Block Design with three replications. The treatment of soybean varieties tested were V1: Anjasmoro variety, V2: Biosoy II variety, V3: Detap variety I, V4: Dega variety I, V5: Dena variety I. The variables observed in this study were: (1) nutrient concentration variables soil (N and P) at 40 days after planting, (2) growth variables included: plant height, number of leaves, dry weight of shoots and roots, plant nutrient uptake at 40 days after planting (N and P), and (3) mycorrhizal population variables included : number of spores and percentage of root infection at 40 days after planting. Observational data were analyzed using analysis of variance followed by the Least Significant Difference test at a significant level of 5%. The results showed that the Anjasmoro (V1) variety showed the best growth in the application of organic, inorganic, and mycorrhizal fertilizers on dry land in North Lombok.